Write the addition equation as a multiplication equation.
8 + 8 +8= 24

Answers

Answer 1
Answer:

Answer:

3 × 8 = 24

3 × 8 is the multiplication equation.

Answer 2
Answer:

Answer:

8x=24

Step-by-step explanation:

Please sayb this was helpful


Related Questions

Which figures demonstrate a single reflection?Select each correct answer.
Television viewing reached a new high when the global information and measurement company reported a mean daily viewing time of hours per household. Use a normal probability distribution with a standard deviation of hours to answer the following questions about daily television viewing per household. a. What is the probability that a household views television between 3 and 9 hours a day (to 4 decimals)? b. How many hours of television viewing must a household have in order to be in the 2%top of all television viewing households (to 2 decimals)? hours c. What is the probability that a household views television more than hours a day (to 4 decimals)?
A city received 2 inches of rain each day for 3 days. The meteorologist said that if the rain had been snow, each inch of rain would have been 10 inches of snow. How much snow would that city have received in the 3 days?
Which expression is equivalent to −2.1+(−5.9)+(−3.7) ?(2.1+5.9)+(−3.7)−(2.1−5.9)+(−3.7)(2.1+5.9+3.7)−2.1−(5.9+3.7)
Will Mark Brainliest! What are the coordinates of point A?(–2, –6)(–6, –2)(–6, –3)(–3, –6)

(1 point) For the given position vectors r(t)r(t), compute the (tangent) velocity vector r′(t)r′(t) for the given value of tt . A) Let r(t)=(cos4t,sin4t)Let r(t)=(cos⁡4t,sin⁡4t). Then r′(π4)r′(π4)= ( , )? B) Let r(t)=(t2,t3)Let r(t)=(t2,t3). Then r′(5)r′(5)= ( , )? C) Let r(t)=e4ti+e−5tj+tkLet r(t)=e4ti+e−5tj+tk. Then r′(−5)r′(−5)= i+i+ j+j+ kk ?

Answers

Answer:

(a)

r'(\frac \pi 4) =(0.-4)

(b)

r'(5)= (10,75)

(c)

r'(-5) =4 e^(-20)\hat i-5e^(25)\hat j+\hat k

Step-by-step explanation:

(a)

Give that,the position vector is

r(t) = (cos 4t, sin 4t)

Differentiating with respect to t

r'(t) = (-4sin 4t, 4 cos 4t)    [(d)/(dt) cos mt = -m \ sin \ mt  and   (d)/(dt) sin mt = m \ cos \ mt]

To find the r'(\frac\pi 4), we put t=\frac \pi4

r'(\frac\pi 4) = (-4sin (4.\frac \pi 4), 4 cos  (4.\frac \pi 4))

        =(0, -4)

(b)

Give that,the position vector is

r(t) = (t²,t³)

Differentiating with respect to t

r'(t) = (2t, 3t²)

To find r'(5) ,  we put t=5

r'(5) = (2.5,3.5²)

      = (10,75)

(c)

Given position vector is

r(t) = e^(4t)\hat i+e^(-5t)\hat j+t\hat k

Differentiating with respect to t

r'(t) =4 e^(4t)\hat i+(-5)e^(-5t)\hat j+\hat k

\Rightarrow r'(t) =4 e^(4t)\hat i-5e^(-5t)\hat j+\hat k

To find r'(-5) ,  we put t= - 5 in the above equation

r'(-5) =4 e^(4.(-5))\hat i-5e^(-5.(-5))\hat j+\hat k

\Rightarrow  r'(-5) =4 e^(-20)\hat i-5e^(25)\hat j+\hat k

For the given position vectors r(t)r(t), compute the (tangent) velocity vector r′(t)r′(t) for the given value of tt  are:

A) r' (\pi /4) = (0, -4) \nB) r'(5) = (10, 75)\nC) r'(-5) = (4e^(-20), -5e^(25), 1)

To compute the velocity vector, we need to find the derivative of the position vector with respect to time (t). This will give us the tangent velocity vector.

A) Let r(t) = (cos⁡4t, sin⁡4t).

To find r'(t), we take the derivative of each component with respect to t:

r'(t) = (d/dt (cos⁡4t), d/dt (sin⁡4t))

r'(t) = (-4sin⁡4t, 4cos⁡4t)

To find r'(π/4), we substitute t = π/4 into r'(t):

r'(π/4) = (-4sin⁡(4(π/4)), 4cos⁡(4(π/4)))

r'(π/4) = (-4sin⁡π, 4cos⁡π)

r'(π/4) = (0, -4)

B) Let \ r(t) = (t^2, t^3).

To find r'(t), we take the derivative of each component with respect to t:

r'(t) = (d/dt (t^2), d/dt (t^3))\nr'(t) = (2t, 3t^2)

To find r'(5), we substitute t = 5 into r'(t):

r'(5) = (2(5), 3(5)^2)\nr'(5) = (10, 75)

C) Letr(t) = e^(4t)i + e^(-5t)j + tk.

To find r'(t), we take the derivative of each component with respect to t:

r'(t) = (d/dt (e^(4t)), d/dt (e^(-5t)), d/dt (t))]\n\nr'(t) = (4e^(4t)), -5e^(-5t), 1)

To find r'(-5), we substitute t = -5 into r'(t):

r'(-5) = (4e^(4{-5}), -5e^(-5(-5)), 1) \n\nr'(-5) = (4e^(-20), -5e^(25), 1)

So, the answers are:

A) r' (\pi /4) = (0, -4) \nB) r'(5) = (10, 75)\nC) r'(-5) = (4e^(-20), -5e^(25), 1)

To know more about vectors:

brainly.com/question/33923402

#SPJ3

PLEASE HELP I MISSED A WHOLE WEEK AND IM SO CONFUSED WHAT THIS IS

Answers

The value of x is given by the pythagoras theorem
X^2 = 17^2 - 15^2
X^2 = 289-225
X^2 = 64
X = sqrt64
X= 8cm

Assume that you have a balance of $5000 on your Visa credit card and that you make no more charges. If your APR is 22% and each month you make only the minimum payment of 3% of your balance, then find a formula for the balance after t monthly payments.A) 5000(0.952217)t

B) 5000(1.011117)t

C) 5000(0.987783)t

D) 5000(1.048883)t

Can someone explain to me how to solve this please

Answers

Answer:

C) 5000(0.987783)^t

Step-by-step explanation:

The monthly interest rate is the APR divided by 12, so is 22%/12 ≈ 0.018333.

Each month, the previous balance (B) has interest charges added to it, so the new balance is ...

balance with interest charges = B + (22%)/12×B = 1.018333×B

The minimum payment is 3% of this amount, so the new balance for the next month is ...

balance after payment = (1.018333B)(1 - 0.03) = 0.987783B

Since the balance is multiplied by 0.987783 each month, after t payments, the balance starting with 5000 will be ...

5000×0.987783^t . . . . . . . . . matches choice C

Find the distance between the point (-18,-19) and the point (-18,16).

Answers

ANSWER

EXPLANATION

To find the distance between the two points, we will use the formula:

\begin{gathered} D=\text{ }\sqrt[]{(x_2-x_1)^2+(y_2-y_1)^2} \n \text{where (x}_1,y_1)\text{ = (-18, -19)} \n (x_2,y_2)\text{ = (-18, 16)} \end{gathered}

So, we have that:

undefined

What is the total? Add those together.

Answers

Answer:

whats the whole question

Step-by-step explanation:

Please help me I’ve been stuck for hours

Answers

Answer/Step-by-step explanation:

Given that a and b are two corresponding sides of two similar figures, it follows that the ratio of their areas = a²/b².

We would use the above knowledge to solve the questions given as follows:

✔️The first pair similar of shapes:

Missing area = x cm²

Therefore,

x/9 = 8²/4²

x/9 = 64/16

x/9 = 4

Cross multiply

x = 4 × 9

x = 36 cm²

✔️The second pair similar of shapes:

Missing area = x cm²

Therefore,

x/240 = 8²/32²

x/240 = 64/1,024

Cross multiply

x*1,024 = 64*240

x*1,024 = 15,360

Divide both sides by 1,024

x = 15,360/1,024

x = 15 cm²

✔️The third pair similar of shapes:

Missing area = x cm²

Therefore,

x/40 = 3²/2²

x/40 = 9/4

Cross multiply

x*4 = 9*40

x*4 = 360

Divide both sides by 4

x = 360/4

x = 90 cm²